Knowledge Networks, Collaboration Networks, and Exploratory Innovation - Wang, Chunlei; Rodan, Simon; Fruin, Mark; Xu, Xiaoyan (Academy of Management Journal, 2014)
Innovation in firms is doubly embedded: in a social network of collaborations between researchers, and in a knowledge network composed of linkages between knowledge elements. The two networks are decoupled. Their structural features are distinct and influence researchers' exploratory innovation differently. Using the patent data of a leading U.S. microprocessor manufacturer, we constructed the firm's collaboration and knowledge networks, and examined the effects of two structural features in the two networks—structural holes and degree centrality—on researchers' exploratory innovation. Our findings show that a researcher with knowledge elements rich in structural holes in the knowledge network tends to explore fewer new knowledge elements from outside the firm, while structural holes in the collaboration network increase exploratory innovation. The average degree centrality of a researcher's knowledge elements in the knowledge network has an inverted-U-shaped relationship with his or her exploratory innovation, while degree centrality in the collaboration network has a negative effect. This study suggests that knowledge and social networks influence where researchers search for discoveries.